Medical Tourism Industry: Its Framework and Impact on the Global Healthcare - Mikava, Nino; Nikoleishvili, Elza (Caucasus Journal of Health Sciences and Public Health, 2018)
The global growth in the flow of patients and health professionals as well as capital funding and medical technology has given rise to the multi billion industry of medical tourism, on the global market. Experts often call it medical tourism Gold Rush, comparing the recent explosive growth and pace of medical tourism participants’ emergence on the international market with California gold rush. Nations’ Governments around the World express interest in cultivating sectors of medical tourism, as a source of lucrative income and an opportunity for economic growth, health system improvement. Experts of the field find big potential and forecast great perspectives in Health and Medical tourism for Georgia. However, the topic is not studied. For this purpose, firstly, scoping review of literature is conducted to overview the best practices in developing and less developed countries, to identify needs and topics to focus for the research, in Georgia. Studies mainly focus on the drivers of medical tourism, with aim to identify which push and pull factors are mostly influencing customers’ decision to travel for the treatment and a choice of the destination country. It shows that, geographical proximity, shorter travel time and ease of barriers in reaching the destination, also familiarity and cultural similarity are significant determinants of the destination country. Moreover, the industry appears to be developing regional hubs that strategically cater services to potential customers in proximity and another well established trend is the reversed flow of medical tourists from developed to developing countries. Governments of all the countries being top destination and successful in medical tourism, have played key role by putting this direction on the top of their agenda, adopted strong measures and enacted policy of promoting medical tourism. Strategic elements for this goal have been: incentives, such as reducing tariffs on imports of equipment for hospitals, incentivizing international accreditation of hospitals through tax free approach, providing incentives or subsidies to attract private sector investment, encouraging cooperation in the public sector between various ministries, developing general tourism infrastructure etc. All-in-all, government’s active involvement and appropriate policy are crucial to utilize resources, to develop inbound medical tourism in Georgia and to be established as a destination country in this highly profitable industry. Furthermore, for this purpose, needs assessment research should be conducted to fill gaps in knowledge and increase certainty about what needs to be done to develop medical tourism in Georgia.